Analysis of the Impact of Profitability and Working Capital on Company Value - Handra Tipa; Neni Marlina Br Purba; Viola Syukrina E Janrosl (Komunitas Dosen Indonesia, 2022)
One very calculated criterion for determining a company's performance is its market value. The more the company value in a corporation, the happier rational investors will be. Investors will feel more comfortable making investments if a company's worth is high enough because it will indirectly result in significant rewards for the investors. Fundamental elements of the business, such as firm capital and profitability ratios, have a significant impact on fluctuations or changes in the value of the company (return on investment). financial ratios such as return on equity (ROE). The worth of the company in the capital market will decline as the financial ratio or the company's profitability as a percentage, which will also reduce investors' interest in the company. The manufacturing firms in the food and beverage industry that were listed on the Indonesia Stock Exchange (IDX) between 2016 and 2020 make up the study's population. The study's findings indicate that although there has been research on working capital and business value, there is no conclusive evidence of a connection. There is a strong correlation between return on assets and company value in the food and beverage industry